2018
DOI: 10.1186/s40169-018-0204-7
|View full text |Cite
|
Sign up to set email alerts
|

Viral antigens detectable in CSF exosomes from patients with retrovirus associated neurologic disease: functional role of exosomes

Abstract: Background HTLV-1 infects over 20 million people worldwide and causes a progressive neuroinflammatory disorder in a subset of infected individuals called HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP). The detection of HTLV-1 specific T cells in the cerebrospinal fluid (CSF) suggests this disease is immunopathologically mediated and that it may be driven by viral antigens. Exosomes are microvesicles originating from the endosomal compartment that are shed into the extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 87 publications
1
69
0
Order By: Relevance
“…Exosomes are small vesicles with a diameter of 40-150 nm [7]. Most model cells secrete exosomes, which contain multiple substances, including large amounts of proteins and nucleic acids, and transport substances to various cells [8][9][10]. The virus enters cells through endocytic pathways during the process of exosome formation and completes its assembly and release [11].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are small vesicles with a diameter of 40-150 nm [7]. Most model cells secrete exosomes, which contain multiple substances, including large amounts of proteins and nucleic acids, and transport substances to various cells [8][9][10]. The virus enters cells through endocytic pathways during the process of exosome formation and completes its assembly and release [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they are present in almost all biological fluids, such as blood, urine, breast milk, cerebrospinal fluid, saliva, semen, etc. [11][12][13][14][15][16][17]. Further characterizations are based on the different sizes and biogenesis of EVs.…”
Section: Biogenesis and Compositions Of Extracellular Vesiclesmentioning
confidence: 99%
“…Apoptotic bodies are much larger, ranging from 800 to 5000 nm in diameter, and are generated by blebbing of plasma membrane from cells undergoing apoptosis. Hence, apoptotic bodies represent the fragments of dying cells and differ from exosomes and microvesicles in property (Figure 1) [17][18][19][20][21][22]. In this chapter, we will collectively term both exosomes and microvesicles as EVs with apoptotic bodies excluded.…”
Section: Biogenesis and Compositions Of Extracellular Vesiclesmentioning
confidence: 99%
“…HAM/TSP causes alteration of CNS axonal transport based on the presence of APP deposits Roles of Semaphorins in Neurodegenerative Diseases DOI: http://dx.doi.org /10.5772/intechopen.82046 in the axons, a classical marker of defects in fast axonal transport [134,135]. Immunological studies have shown a chronic infiltration of activated CD4+ and CD8+-T-cells into the CNS [136].…”
Section: Spastic Paraparesis Associated To Htlv-1mentioning
confidence: 99%
“…In the cytoplasm of infected lymphocytes, Tax activates NF-kB pathway responsible for proliferation and differentiation of T-cells, whereas in the nucleus, Tax activates the ATP/CREB pathway. Tax can also be secreted via endoplasmic reticulum-Golgi apparatus and by exosomes [136][137][138][139][140][141]. Tax secreted from activated peripheral blood mononuclear cells (PBMCs) could explain the presence of Tax in the plasma and CSF of infected patients and carriers [141].…”
Section: Spastic Paraparesis Associated To Htlv-1mentioning
confidence: 99%